Spectroscopy of post-AGB star IRAS 01005+7910 - Nasonov, D.S. (Advances in Astronomy and Space Physics, 2011)
Infrared source IRAS 01005+7910 is identified with an 11-mag peculiar star which has been previously found to be a post asymptotic giant branch star of early spectral type. There is significant spectral variability detected earlier. Over 30 spectra were obtained with high resolution (15000 − 60000) in spectral range 3500 − 7800 ˚A˚A. In this work the results of the spectral monitoring of this object are presented. The detailed analysis of radial velocities was carried out. Radial velocities derived from different absorption lines show variability within the same spectrum. Significant variability of radial velocities is demonstrated on the scale of one day. The variability of line profiles is present. The constant radial velocity −51 ± 1.4 km/s of forbidden lines was detected. Shell expansion velocity is estimated from widths of forbidden emission line profiles. The hydrogen and helium line profiles demonstrate the complicated and changing picture both of accretion and outflow in envelope.